Influence of the addition of montmorillonite to the matrix of unidirectional glass fibre/epoxy composites on their mechanical and water absorption properties - Manfredi, Liliana Beatriz (2008)
Epoxy nanocomposites were used as matrix of glass fibre-reinforced composites. The dispersion of the clay in the epoxy was studied by X-ray diffraction analyses given strong evidence that the clay formed an intercalated structure in the polymer. An increment in the mechanical properties after the addition of clay in the epoxy matrix was observed in the composites. The water absorption curves at 80 °C fitted a two-step diffusion model, where the first step was diffusion controlled and the second one was associated with the molecular motion and relaxation process of the polymer chains. The composites containing a nanocomposite matrix absorbed higher quantity of water at long times than the one with a pure epoxy matrix due to the diminution in the crosslinking density of the epoxy. A diminution in the mechanical properties after water submersion as well as a detrimental effect of the water on the matrix and interface of the composites was observed.